Students’ Responses to the Implementation of Role Play in Learning Greetings and Manners in an EFL Boarding School - Yanuarista Sukranekaputri; Weningtyas Parama Iswari; Noor Rachmawaty (Universitas Pendidikan Ganesha, 2026)
This qualitative study examines how students responded to the use of role play in learning greetings and manners in an EFL classroom at a boarding junior high school. Data were gathered from three main sources: classroom observations that focused on students’ communicative performance, teachers’ reflective notes that recorded social and interactional responses, and students’ written reflections that captured their personal experiences of the learning process. The findings were grouped into three main themes. First, students’ communicative performance showed gradual improvement across learning sessions, particularly in vocal clarity, intonation, and their awareness of when to use formal or informal expressions. Second, role play encouraged positive social and interactional behaviors, including cooperation, peer support, and the emerging use of appropriate non-verbal cues during interaction. Third, students described role play as an engaging and meaningful activity that helped them understand how language is used in real-life situations, even though they still faced challenges such as limited vocabulary and initial anxiety. Based on these findings, it can be concluded that role play generated positive linguistic, social, and affective responses from students while providing a supportive space for developing communicative competence in learning greetings and manners. The results further indicate that role play can function as an effective pedagogical approach for promoting contextualized language use and sustained student engagement in EFL classrooms.